Exploring community perspectives and initiatives for environmental sustainability toward a proposed 5-year corporate social responsibility plan in Mariveles, Bataan - Arlene A. Zabala (CV. Literasi Indonesia, 2026)
This qualitative study explores community perceptions of environmental conditions and sustainability initiatives in selected barangays of Mariveles, Bataan. Utilizing semi-structured interviews and focus group discussions with 30 residents from Barangays Alas-Asin, Baseco, and Sisiman, the research aims to understand local perspectives on water quality, air quality, and community engagement in environmental efforts. Thematic analysis revealed several key findings: participants expressed significant concerns about access to safe water sources and air quality, linking these issues directly to their health and well-being. A strong sense of personal responsibility for environmental stewardship was evident; however, barriers such as time constraints and limited awareness hindered active participation in local initiatives. The study also highlighted the importance of education and communication from local authorities to foster greater community involvement. Participants suggested regular community clean-up drives, enhanced educational programs on sustainability, and improved collaboration with local organizations as effective strategies for addressing environmental challenges. Based on these insights, a five-year Corporate Social Responsibility (CSR) plan titled “Kilos-Lakas-Kalikasan” is proposed to establish a structured partnership between GNPower and the community, focusing on collaborative projects aimed at enhancing environmental protection. This research contributes to understanding the role of community engagement in sustainability efforts and offers actionable recommendations for improving environmental conditions in Mariveles.